The Limits of Affluence: Welfare in Ontario, 1920-1970 - Nelles, H. V. (Labour / Le Travail, 1996)
The article reviews the book "The Limits of Affluence: Welfare in Ontario 1920-1970," by James Struthers.
Keywords: BOOKS – Reviews; LIMITS of Affluence: Welfare in Ontario 1920-1970; The (Book); Nonfiction; PUBLIC welfare; STRUTHERS; James